Encapsulation of B. bassiana in Biopolymers: Improving Microbiology of Insect Pest Control - Felizatti, Ana Paula; Manzano, Roberta Maria; Rodrigues, Inajá Marchizeli Wenzel; da Silva, Maria Fátima das Graças Fernandes; Fernandes, João Batista; Forim, Moacir Rossi (Frontiers in Microbiology, 2021)
Beauveria bassiana is widely used for pest control. Biostability and dispersion for broth pulverization, however, are limiting factors for its application in the field. In this context, formulation techniques such as microencapsulation are viable alternatives. The aim of this work is to optimize B. bassiana formulations by spray dryer and evaluate its stability and biological activity against Spodoptera cosmioides compared to ionic gelatinization formulations. The fungus was biocompatible with all evaluated biopolymers (lignin, cellulose, starch, humic substances, and alginate). The encapsulation by spray drying was optimized by factorial design in an inlet and outlet air temperature of 120 and 68 ºC, respectively; aspirator rate 35 m3h-1, feed flow rate 12 mLmin-1; and drying gas flow at 35 Lh-1. The ionic gelation capsules were obtained using a 0.5% quantity of conidia in a 1% sodium alginate solution, which was dropped into a 0.5 mol·L-1 CaCl2 solution using a peristaltic pump. Spray drying provided smaller microcapsules than those by ionic gelation. Both techniques produced more stable conidia when exposed to temperature and UV-radiation than non-formulated B. bassiana. The formulations prepared by spray drying showed gains at aqueous dispersion. Biological assays against Spodoptera cosmioides showed a mortality rate of up to 90%. These results demonstrate the suitability of encapsulating B. bassiana conidia stably in aqueous dispersion without loss of viability and virulence.